Plasma Amino Acids Metabolomics' Important in Glucose Management in Type 2 Diabetes - Alqudah, Abdelrahim; Wedyan, Mohammed; Qnais, Esam; Jawarneh, Hassan; McClements, Lana (Frontiers in Pharmacology, 2021)
The perturbation in plasma free amino acid metabolome has been observed previously in diabetes mellitus, and is associated with insulin resistance as wellnd the onset of cardiovascular disease (CVD) in this population. In this study, we investigated, for the first time, changes in the amino acid profile in a group of people with and without type 2 diabetes (T2D) with normal BMI, from Jordan, who were only managed on metformin. Twenty one amino acids were evaluated in plasma samples from 124 people with T2D and 67 healthy controls, matched for age, gender and BMI, using amino acids analyser. Total amino acids, essential amino acids, non-essential amino acids and semi-essential amino acids were similar in T2D compared to healthy controls. Plasma concentrations of four essential amino acids were increased in the presence of T2D (Leucine, p<0.01, Lysine, p<0.001, Phenylalanine, p<0.01, Tryptophan, p<0.05). On the other hand, in relation to non-essential amino acids, Alanine and Serine were reduced in T2D (p<0.01, p<0.001, respectively), whereas Aspartate and Glutamate were increased in T2D compared to healthy controls (p<0.001, p<0.01, respectively). A semi-essential amino acid, Cystine, was also increased in T2D compared to healthy controls (p<0.01). Citrulline, a metabolic indicator amino acid, demonstrated lower plasma concentration in T2D compared to healthy controls (p<0.01). These amino acids were also correlated with fasting blood glucose and HbA1c (p<0.05). Glutamate, glycine and arginine were correlated with the duration of metformin treatment (p<0.05) whereas no amino acids were correlated with lipid profiles. Disturbances in the metabolism of these amino acids are closely implicated in the pathogenesis of T2D and associated cardiovascular disease (CVD). Therefore, these perturbed amino acids should be explored as therapeutic targets to improve T2D management and prevent associated cardiovascular complications.